Genetic variability of wild palms Euterpe precatoria, Euterpe oleracea and Mauritia flexuosa with molecular markers ISSR - Morillo-Coronado, Yacenia; Rojas-González, Salvador; Morillo-Coronado, Ana Cruz; Castañeda-Cardona, Christian Camilo; Mendoza-Romero, Karem Julieth; Marín-Colorado, Jaime (Revista de Ciencias Agrícolas, 2023)
Wild palms constitute a group of plants of particular economic importance in the tropics, being a valuable source for obtaining construction materials, fabrics, fuel, food, ornamental and medicinal plants. Despite their economic, social, and environmental importance, the genetic variability existing in wild palms, mainly of the genus Mauritia and Euterpe, is unknown, which limits their potential use and the identification of promising genotypes to be included in recombination programs. The genetic variability of three wild palm species (Euterpe oleracea, Euterpe precatoria, and Mauritia flexuosa) was evaluated using Inter-Simple Sequence Repeat (ISSR) markers. A total of 51 genotypes were analyzed with seven ISSR primers, which generated a total of 153 bands, with a percentage of polymorphic loci of 90.24%. The cluster analysis revealed the formation of six groups at a similarity level of 37%, grouping the palm genotypes by species and geographical origin. Molecular variance analysis revealed that within group variations contributed more to genetic diversity (89%) than between group variations (11%). The average value of Fst was 0.20, demonstrating moderate genetic differentiation. The high genetic variability found in this study indicates the valuable genetic potential present in palm germplasm, which could be used for future improvement programs of the species.